Improvement of artemisinin content through mutation of in vitro shoot cultures of Artemisia cinamedicinal plant - Aryanti . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Improvement of plant traits through mutation induction of herbal medicine of shoots Artemisia cina in vitro have conducted by gamma rays. About 200 of A.cina shoots in vitro were cultured in Murashige & Skoog(MS) medium without phyto-hormone were irradiated by the dose of 10 Gy at Gamma Chamber in PATIR – BATAN. Irradiated shoot cultures were then multiplication and selected. The selected mutant lines have acclimatized and cultivated at distance of 0.5 x 1 m at Bogor region. 21 of mutant lines have been obtained from 630 A.cina mutant lines from field cultivation. The morphological observation i.e., leaves area, plants high and percentage of flower emerge have conducted when the plants were cultivated in the field. The artemisinin content of mutant lines and original plant have conducted by using HPLC. The result shown that the mutant lines had higher leaves area than original plant and some of mutant lines were shorter than original plant. The percentage of emerge flowers were reached 50.17% to be A31.1 mutant line. The improvement of plant traits by gamma rays was showed by increasing of artemisinin in A.cina mutant lines. The highest artemisinin content to be A32a2, A32c1 and A36.2 were found 21.03 mg/g, 19.99 and 15.79 mg/g respectively compared to the original plant only 0.40 mg/g. The improvement of artemisinin content of mutant line A32a2, A32c1 and A36.2 were 52.25; 48.97 and 38.48% respectively.Key word :mutation, shoots in vitro, artemisinin, Artemisia cina